2013
DOI: 10.1039/c3cp51011e
|View full text |Cite
|
Sign up to set email alerts
|

Unusual molecular material formed through irreversible transformation and revealed by 4D electron microscopy

Abstract: Four-dimensional (4D) electron microscopy (EM) uniquely combines the high spatial resolution to pinpoint individual nano-objects, with the high temporal resolution necessary to address the dynamics of their laser-induced transformation. Here, using 4D-EM, we demonstrate the in situ irreversible transformation of individual nanoparticles of the molecular framework Fe(pyrazine)Pt(CN) 4 . The newly formed material exhibits an unusually large negative thermal expansion (i.e. contraction), which is revealed by time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…The remaining material still displays a thermal expansion behavior. Indeed, it was shown that under certain favorable conditions, the Fe(pyrazine)Pt(CN) 4 nanoparticles can undergo a chemical transformation that involves the removal of pyrazine molecules from the 3D framework structure 52 . The remaining crystalline material does no longer display SCO, but it exhibits an exceptionally large negative thermal expansion coefficient in the a , b -plane.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining material still displays a thermal expansion behavior. Indeed, it was shown that under certain favorable conditions, the Fe(pyrazine)Pt(CN) 4 nanoparticles can undergo a chemical transformation that involves the removal of pyrazine molecules from the 3D framework structure 52 . The remaining crystalline material does no longer display SCO, but it exhibits an exceptionally large negative thermal expansion coefficient in the a , b -plane.…”
Section: Resultsmentioning
confidence: 99%
“…Ångstroms-micrometers (Å-ÎŒm) and femtoseconds-nanoseconds (fs-ns), respectively. In this regard, ultrafast electron microscopy (UEM) has recently emerged as a powerful technique for the study of ultrafast photoinduced processes in nanoscale systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . The material is excited by a short fs-ns laser pulse, which is followed by a similarly short electron pulse that probes the ensuing dynamics by means of imaging, diffraction, or spectroscopy inside a transmission electron microscope (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] In order to both understand these switching mechanisms and to design efficient integrated ST materials, grafting Fe(II) compounds to nanoparticles provides a relevant approach for experimentation. 31,32 Furthermore, ST polymeric chains of [Fe(aminotriazole) 3 ] n 2+ compounds have been processed into composite nanoparticles showing the consistency of their properties. 29,30 The photocommutation of three-dimensional Hoffmann clathrate [Fe II (pyrazine)][Pt(CN) 4 ] n nanocrystals has also been achieved and studied by 4D electronic microscopy.…”
Section: Introductionmentioning
confidence: 99%